2011
DOI: 10.1109/jqe.2011.2107889
|View full text |Cite
|
Sign up to set email alerts
|

Dense-Coding Attack on Three-Party Quantum Key Distribution Protocols

Abstract: Cryptanalysis is an important branch in the study of cryptography, including both the classical cryptography and the quantum one. In this paper we analyze the security of two three-party quantum key distribution protocols (QKDPs) proposed recently, and point out that they are susceptible to a simple and effective attack, i.e. the dense-coding attack. It is shown that the eavesdropper Eve can totally obtain the session key by sending entangled qubits as the fake signal to Alice and performing collective measure… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…Thus far, many MQCP-CDs [34,35,[55][56][57] have been attacked since the unitary operations used in those protocols can be discriminated unambiguously (by a single use) if an eavesdropper utilizes some special attack strategies, such as dense-coding attack [35] and fake-signal attack. [55] It is just because there is still no effective method for constructing the required unitary operations that some improper ones were used in those protocols.…”
Section: Methods For Constructing the Unitary Operations Required In ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Thus far, many MQCP-CDs [34,35,[55][56][57] have been attacked since the unitary operations used in those protocols can be discriminated unambiguously (by a single use) if an eavesdropper utilizes some special attack strategies, such as dense-coding attack [35] and fake-signal attack. [55] It is just because there is still no effective method for constructing the required unitary operations that some improper ones were used in those protocols.…”
Section: Methods For Constructing the Unitary Operations Required In ...mentioning
confidence: 99%
“…On the other hand, this strategy can also reduce the hardware requirement for the implementation of the protocol, since all the users (except for the center who is responsible for preparing and measuring states) only need to perform certain unitary operations in the whole executing procedure of the protocol. To date, much attention has been focused on the collective detection strategy and a lot of MQCPs have been proposed by utilizing it (for simplicity, we will call the MQCP which uses collective detection MQCP-CD), [34][35][36][37][38][39][40][41] including QKD, [34][35][36] QPC, [37] QSS, [38][39][40] and QSQC. [41] In an MQCP-CD, all the users (except for the center) just need to be capable of performing certain unitary operations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, it has been identified that QKD itself is vulnerable to denial of service (DoS) attacks [16]. Any attempt to learn keys on quantum optical equipment causes noise, potentially leading to the exhaustion of keys.…”
Section: Transactions On Ieeementioning
confidence: 99%
“…As pointed out by Lo and Ko, breaking cryptographic systems was as important as building them [26]. In the study of quantum cryptography, quite a few effective attack strategies have been proposed, such as intercept-resend attacks [27], entanglementswapping attacks [28,29], teleportation attacks [30], densecoding attacks [31][32][33], channel-loss attacks [34,35], denialof-service attacks [36,37], correlation-extractability attacks [38][39][40], Trojan horse attacks [41,42], and participant attacks [29,33]. Understanding those attacks will be helpful for us to design new schemes with high security.…”
Section: Introductionmentioning
confidence: 99%